The use of audio-visual media: how does it affect rhythmic movement skills? - Hardinata, Riyan; Fakhruddin, Fakhruddin; Syarif, Ahmad; Ahwan, M Tami Rosadi; Abidin, Muhamad Zainal; Alamsyah, Alamsyah; Abdulrahman, Dimas; Shukla, Manish; Malek, Nor Fazila Abd; Sa'adah, Shofi Putri (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. Audio-visual media is a tool for conveying information used in learning in the form of sound and image messages. This study aims to determine the effectiveness of using audio-visual media to improve rhythmic movement skills.Material and Methods. The study used an experimental method using a one group pretest and posttest design. Students in this study were given treatment in the form of audiovisual media. The subjects of this study were grade V students of State Elementary School 4 Tebas Sambas Regency, totaling 27 people, consisting of 13 male students and 15 female students. The sampling technique used was total sampling. Data collection instruments use non-test instruments in the form of performance observations. The SPSS version 26 application was used to help with data analysis in this investigation.Results. The results showed a significance value of 0.000 <0.05, so the data can be said to be significant. Based on these results, it can be concluded that the use of audiovisuals to develop rhythmic movement skills in students shows significant effectiveness.Conclusions. These results provide evidence that audiovisual media can be applied to improve rhythmic movement skills in students, especially in elementary schools.